Preparation of thermoplastic container via thermoforming process - Nik Ruqiyah, Nik Hassan (2015)
Thermoforming process is one of the processes used in fabrication of plastic part. Thermoforming process is a process of changing flat thermoplastic sheet to three dimensional shapes. The type of thermoforming process used in this project is vacuum forming. Thermoforming process rarely used in industry of fabrication thermoplastic container. Thermoplastic are plastic that softened and can form any shape using heat and its return to a solid upon cooling. The thermoplastic material type used in this project is Polypropylene (PP). The properties of this (PP) material are economical material, good and resistance to fatigue. Therefore, the main objective of this study to prepare the thermoplastic container by using thermoforming process. In preparation of this thermoplastic container, the design and fabricate the mould is the important process to produce good container. The difference temperature used to identify the suitable temperature used in thermoforming process. The temperature used start with 160⁰c until 200⁰c. The result shows the suitable temperature in range 165⁰c-170⁰c.